FEMA GRAS assessment of derivatives of basil, nutmeg, parsley, tarragon and related allylalkoxybenzene-containing natural flavor complexes. (May 2023) - Davidsen, Jeanne M.; Cohen, Samuel M.; Eisenbrand, Gerhard; Fukushima, Shoji; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Rosol, Thomas J.; Harman, Christie L.; Taylor, Sean V.
Abstract: In 2015, the Expert Panel of the Flavor and Extract Manufacturers Association (FEMA) initiated a program for the re-evaluation of the safety of over 250 natural flavor complexes (NFCs) used as flavoring ingredients in food. In this publication, tenth in the series, NFCs containing a high percentage of at least one naturally occurring allylalkoxybenzene constituent with a suspected concern for genotoxicity and/or carcinogenicity are evaluated. In a related paper, ninth in the series, NFCs containing anethole and/or eugenol and relatively low percentages of these allylalkoxybenzenes are evaluated. The Panel applies the threshold of toxicological concern (TTC) concept and evaluates relevant toxicology data on the NFCs and their respective constituent congeneric groups. For NFCs containing allylalkoxybenzene constituent(s), the estimated intake of the constituent is compared to the TTC for compounds with structural alerts for genotoxicity and when exceeded, a margin of exposure (MOE) is calculated. BMDL10 values are derived from benchmark dose analyses using Bayesian model averaging for safrole, estragole and methyl eugenol using EPA's BMDS software version 3.2. BMDL10 values for myristicin, elemicin and parsley apiole were estimated by read-across using relative potency factors. Margins of safety for each constituent congeneric group and MOEs for each allylalkoxybenzene constituent for each NFC were determined that indicate no safety concern. The scope of the safety evaluation contained herein does not include added use in dietary supplements or any products other than food. Ten NFCs, derived from basil, estragon (tarragon), mace, nutmeg, parsley and Canadian snakeroot were determined or affirmed as generally recognized as safe (GRAS) under their conditions of intended use as flavor ingredients based on an evaluation of each NFC and the constituents and congeneric groups therein. Highlights: Safety evaluation of natural flavoring complexes. Evaluation used procedure developed by the FEMA Expert Panel for natural flavor complexes. FEMA GRAS status determined/affirmed for 10 natural flavor complexes.